Konversi Eugenol dan Isoeugenol menjadi 2-Metoksi-4-propilfenol melalui Reaksi Hidrogenasi Menggunakan Katalis Logam Pt, Pd, dan Ni dalam Zeolit - Asep Kadarohman; Hardjono Sastrohamidjojo; Muhamad Muchalal (Institut Teknologi Bandung, 2009)
2-Methoxy-4-propylphenol is a subtance which could be used to synthesize 1,2-dimethoxy-4-propylbenzena, male fruit fly pheromone (Dacus dorsalis Hendel) which was 50% more effective than methyl eugenol. 2-Methoxy-4-propylphenol could be synthesized from eugenol or isoeugenol by hydrogenation due to their similar structures. This research investigated the conversion selectivity of eugenol or isoeugenol hydrogenation to 2-methoxy-4-propylphenol. The hydrogenation was conducted using various catalyst and metal concentrations of Pt, Pd, and Ni, either in a single form or in combination which was impregnated on X or Y zeolites. The products were analyzed by GC, GC-MS, and FTIR. The result indicated that eugenol was easily hydrogenated than isoeugenol. Pd/Y as a catalyst was more effective than Ni/Y, Pt/Y or combined metal (Pt,Pd,Ni)/X. The highest conversion selectivity occured in 6% catalyst of Pd(10%)/Y that produced 98.24% of 2-methoxy-4-propylphenol.